Modeling and control of flexible context-dependent manufacturing systems - Lucas Silva, André; Ribeiro, Richardson; Teixeira, Marcelo (Information sciences, 2017)
•Modeling of flexible manufacturing systems using extended automata.•Use of extended automata as a modeling mechanism for context-recognition.•Control decisions taken for context-dependent processes.•Methodology for modeling and control with extended automata.•Examples of dynamic context-switching manufacturing systems. In emerging Manufacturing Systems (MSs), flexibility is a key issue. It is related to the ability for a MS to recognize the context and switch its workflow accordingly. Although the literature has provided automated options to model and control MSs, programming context-dependent controllers remains challenging. This is an event-based construction that integrates a large and intricate combination of events and states in order to make the controller flexible, i.e., include context-sensitiveness strategies subject to switching at runtime. Without self-adaptation, each system configuration may require an entire control solution to be recalculated, which implies redesigning the whole modeling and implementation structures. This paper shows that a system model can nevertheless be enriched with elements collected from the context, which optimizes the design of formula-based constraints that can then be integrated to control frameworks for synthesis and code generation. The result is a controller that recognizes the context and takes control decisions accordingly. Examples are provided to illustrate the approach.